The Effect of Working Capital Turnover on the Performance of Coal Companies Listed on the Indonesia Stock Exchange in 2020-2022 - Tripermata, Lukita; Yeni, Yeni; Putra, Mgs. Prima Darma (Jurnal Ecoment Global, 2024)
Abstract Objective: The purpose of this study is to determine the effect of working capital turnover on the company's financial performance. In addition, to find out the elements included in working capital, namely cash turnover, receivables turnover, and inventory turnover to the company's financial performance. Design/Methods/Approach: The research method is quantitative descriptive. The population of this study is 27 coal companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sample of this study uses a sampling technique using the purposive sampling method and the number of samples obtained were as many as 16 companies. Data analysis techniques using the Statistical Product and Service Solutions (SPSS) program. Findings: Working capital turnover and inventory turnover have a significant effect on financial performance. However, cash turnover and receivables turnover did not have a significant effect on financial performance. Originality/Value: This study contains a complete list of publications on working capital turnover and their classification according to various attributes. This research study will be useful for researchers, finance professionals and others who examine the importance of working capital turnover and the conceptualization of corporate finance as a whole. The author intends to develop a Systematic Literature Review (SLR) method in detail on the topic of the relationship between working capital turnover and financial performance, along with elements that include previous working capital turnover published in academic journals. Practical/Policy implication: The sample of this study is only on coal companies listed on the Indonesia Stock Exchange for the period of 2020-2022. Further research can test samples of companies in other manufacturing fields, such as State-Owned Enterprise (SOEs). Further research is suggested to add a longer period of research years. For companies, they can further optimize cash and receivables turnover so that they can be managed more effectively and efficiently to improve financial performance. Keywords: cash turnover, inventory turnover, financial performance, receivables turnover, working capital turnover